Społeczna i poznawcza tożsamość socjologii medycyny w ujęciu Eliota Freidsona - Piątkowski, Włodzimierz; Zalewska-Blechar, Patrycja (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
Eliot Freidson is considered a pioneer and co-founder of classical medical sociology. His research in the 1960s helped establish the notion of repetitive behaviors. It relates health to various dimensions of human functioning: family, community, workplace etc. The initiators and implementers of these behaviors are ordinary people who look for health-related knowledge and advice among their family and friends. This interplay of interactive behaviours creates what Freidson named the “lay referral system”. The aim of this article is to describe and interpret Freidson’s concepts and the ways of their adaptation to Polish medical sociology. Selected examples of sociomedical research inspired by Freidson’s conception prove that his model of interpreting the social field demarcated by the boundary concepts of health – desease – medicine retains its research attractiveness and relevance.